Eco-profiles and economic performances of a high-value fruit crop in southern Italy: a case study of bergamot (Citrus bergamia Risso). Issue 9 (26th November 2017) - Strano, A.; Falcone, G.; Nicolò, B. F.; Stillitano, T.; De Luca, A. I.; Nesci, F. S; Gulisano, G.
ABSTRACT: This paper analyses the environmental and economic sustainability of bergamot, a citrus crop considered very significant for its long-standing peculiarities linked to a strong socio-economic role, a meaningful rooting in territorial heritage and an important function in environmental and landscape terms. A comparison between conventional and organic cropping systems has been carried out by means of life cycle assessment and life cycle costing tools in order to assess the impacts of different management practices. The results show positive performances of the organic production system, from both environmental and economic points of view. Furthermore, compared to similar studies of other citrus crops in the same area, bergamot cultivation can represent an economically sustainable choice for farmers with lower environmental impacts.